"Assessing the opportunities of the Libyan tourism sector to success in developing the local environment in light of the international competition data "Negatives and treatment - Al - Ghazwani, Nasser Abdul Karim (Arab Journal for Sciences and Research Publishing, 2015)
The research examines the reality and possibilities of the Libyan tourism sector in developing the local environment, in light of the characteristics and advantages of this sector that enable it to compete internationally, related to international competition among different countries in terms of economic, educational, , Legal and regulatory .... etc, "and the role of these general indicators in the development of the tourism sector. The importance of this research is that the tourism sector in Libya suffers from the scarcity and lack of specialized studies that are looking at its components and methods of eliminating the negative aspects surrounding it in order to revitalize the environment and strengthen the local economy in general. The study focuses on reviewing the shortcomings of the Libyan state regarding negligence and ignoring the development of the tourism sector in spite of the huge tourism resources available in Libya. This review is to be done through several hypotheses related to the negative aspects related to the development and rehabilitation of the tourism sector in Libya " The occurrence of political unrest and the deterioration of the state. " The research concludes that Libya has huge tourism potential that has not been planned to be exploited optimally or even the promotion of the country has not been considered abroad. The research also concludes that the Libyan economy is an underdeveloped economy that suffers from double standards, This is explained by the significant decline in the ranking of the State of Libya in terms of the various indicators recorded in the report of the competitiveness of tourism and the tourism sector. Far International "2011" for both Western countries or even Arab countries. The research also concludes that the Libyan state did not have any significant role in contributing to the development of tourism in terms of the absence of policies and legislation to enable the public sector to play its role properly in exploiting the tourism components and thus the absence of any economic or tourist plans, Full disappearance of the role of the private sector, complementing the role of the public sector in tourism development, and this complete disappearance of the role of the private sector lies because of the direction of the socialist state so that the role of the private sector was almost abolished by the end of the seventies of the last century. The research considers among the most important analyzes that the chances of recovery of the Libyan economy lies on the revitalization of the tourism sector in a manner that leads to the various economic interactions within the country "tourism industry composite" and the development of the local environment through the development of various economic sectors, "the most important sectors of transport and services and communications, As well as the elimination of several economic problems, the most important of which is economic stagnation and unemployment, as tourism is a labor-intensive industry.